Designing A Use Case Diagram for Developing An Electricity Consumption (EC) System - Rahman S.A.; Binti Hashim W.; Yusof A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Unified Modeling Language; Electricity bill; Electricity usage; Electricity-consumption; Energy usage; Graph layout; Online customers; UML Model; Use case diagram; Electric power utilization